Optimization of Chitosan-PEG/ZnO Hydrogel Formulation with Pomegranate Peel Extract as an Alternative for Wound Healing - Assauqi, Niamul Faza; Lusiana, Retno Ariadi; Masruchin, Nanang (Indonesian Journal of Chemistry, 2025)
A chitosan-zinc oxide (ZnO)/poly(ethylene glycol) (PEG)/pomegranate peel extract (PE) based hydrogel has been developed as a potential material to accelerate the wound healing process by controlling the drug release mechanism. ZnO nanoparticles with an average size of about 95 nm were synthesized using the coprecipitation method and then combined into chitosan/PEG composites to improve the antimicrobial properties of the hydrogels. Characterization of the hydrogels included analysis of size, morphology, elemental composition, microstructure, swelling behavior, antibacterial activity, and wound healing effectiveness. The results of the in vitro study indicated that the antibacterial activity of PE-containing hydrogel against Escherichia coli and Staphylococcus aureus decreased due to the chelation effect caused by PE addition. However, in vivo tests for 10 d showed that the PE-containing hydrogel had better wound healing ability than commercial betadine. In addition, the developed hydrogel showed high biocompatibility with excellent antibacterial activity. This study confirmed that chitosan/PEG/ZnO nanoparticle hydrogel has the potential as wound dressing materials with sustained drug release and optimal healing effectiveness.